2017
DOI: 10.3390/ijms19010084
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling and Physiological Analysis of Haloxylon ammodendron in Response to Osmotic Stress

Abstract: Haloxylon ammodendron, a perennial xero-halophyte, is an essential species for investigating the effects of drought on desert tree. To gain a comprehensive knowledge on the responses of H. ammodendron to drought stress, we specially performed the molecular and physiological analysis of H. ammodendron in response to −0.75 MPa osmotic stress for six and 24 h in lab condition via RNA-seq and digital gene expression (DGE). In total, 87,109 unigenes with a mean length of 680 bp and 13,486 potential simple sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 84 publications
(116 reference statements)
0
7
0
Order By: Relevance
“…Photosynthetic pigments such as chlorophyll a and b decreased during glucose and sorbitol exposure (Fig 7B), suggesting that in P. patens these parameters are more sensitive to high glucose than the maximal rate of PSII, also indicating that the moss is not under optimal operating conditions. In contrast to vascular plants [109][110][111][112], P. patens seems to be less sensitive to osmotic-and glucose-induced photosynthetic inhibition. The biological significance of these differences in photosynthetic activities between vascular and non-vascular plants in response to glucose deserves deeper research.…”
Section: The Regulation Of Photosynthesis In Response To Feeding Glucosementioning
confidence: 76%
See 1 more Smart Citation
“…Photosynthetic pigments such as chlorophyll a and b decreased during glucose and sorbitol exposure (Fig 7B), suggesting that in P. patens these parameters are more sensitive to high glucose than the maximal rate of PSII, also indicating that the moss is not under optimal operating conditions. In contrast to vascular plants [109][110][111][112], P. patens seems to be less sensitive to osmotic-and glucose-induced photosynthetic inhibition. The biological significance of these differences in photosynthetic activities between vascular and non-vascular plants in response to glucose deserves deeper research.…”
Section: The Regulation Of Photosynthesis In Response To Feeding Glucosementioning
confidence: 76%
“…patens these parameters are more sensitive to high glucose than the maximal rate of PSII, also indicating that the moss is not under optimal operating conditions. In contrast to vascular plants [ 109 112 ], P . patens seems to be less sensitive to osmotic- and glucose-induced photosynthetic inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have underlined the role of lipid homeostasis for tumour development and progression. In a study performed in 20 patients, the level of PUFA was significantly lower compared to healthy liver tissue 47 . More recently, cholesterol was also found to be essential for cancer cell metabolism and was proposed as a promising therapeutic target 48 .…”
Section: Discussionmentioning
confidence: 87%
“…MAPK44/42 is widely expressed and is involved in the regulation of meiosis, mitosis, and postmitotic functions in many differentiated cell types. Several different stimuli, including growth factors, cytokines, and viruses can activate the MAPK44/42 pathway (Li and Zhang 2017 ; Ma et al 2010 ). Previously and in the present study, we have found that MAPK/MEK1/2 inhibitor, PD98059 can attenuate elevated phosphorylated MAPK44/42 expression levels in Cd-exposed ht-UtLM cells indicating that MAPK plays an important role in Cd’s proliferative effects.…”
Section: Discussionmentioning
confidence: 99%